2012
DOI: 10.1016/j.biombioe.2012.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Rapid molecular screening of black carbon (biochar) thermosequences obtained from chestnut wood and rice straw: A pyrolysis-GC/MS study

Abstract: Rice straw and chestnut wood were heated between 200 and 1000 °C (T CHAR ) to produce Black C 'thermosequences'. The molecular properties of the charred residues were assessed by pyrolysis-GC/MS to investigate the relation between charring intensity and pyrolysis fingerprint. Samples obtained at T CHAR > 500 ºC (wood) or > 700 ºC (straw) gave low quality pyrograms and poor reproducibility because of high thermal stability, but pyrolysis-GC/MS allowed to track the thermal degradation of the main biocomponents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 75 publications
2
38
1
Order By: Relevance
“…6) which can be explained by volatilization into gaseous form [22], in addition to the loss of N functional groups with carbonization [37,40]. However in the mid-pyrolysis temperature range (500 Ce600 C) it is clear that there is little additional loss of N. Instead it is observed that N is retained and progressively incorporated into recalcitrant structures within the biochar.…”
Section: Black Nitrogen and Stable Polycyclic Aromatic Nitrogen (Span)mentioning
confidence: 82%
“…6) which can be explained by volatilization into gaseous form [22], in addition to the loss of N functional groups with carbonization [37,40]. However in the mid-pyrolysis temperature range (500 Ce600 C) it is clear that there is little additional loss of N. Instead it is observed that N is retained and progressively incorporated into recalcitrant structures within the biochar.…”
Section: Black Nitrogen and Stable Polycyclic Aromatic Nitrogen (Span)mentioning
confidence: 82%
“…Lipids were found to always be a minor component, but were more important in the rice char. When char formed > 700°C, the dominant component was SPAC, which led to low quality pyrograms and poor reproducibility (Kaal et al, 2012).…”
Section: Sources Of Spac and Pyc Slmentioning
confidence: 99%
“…levoglucosan) into larger PAH compounds. Kaal et al (2012) investigated the pyrolysis products from a thermosequence of rice and chestnut wood using flash pyrolysis gas chromatography-mass spectrometry (GC-MS); the components investigated were largely PyC SL . Low temperature PyC components were dominated by carbohydrate and lignin, with lignin-indicative pyrograms more important at mid-range formation temperature.…”
Section: Sources Of Spac and Pyc Slmentioning
confidence: 99%
“…We can presume that a dominant non-BCHyPy fraction was formed at 340-400 °C by unimolecular cyclization, dehydrogenation, dealkylation, and aromatization reactions of wood constituents (lignin, hemicellulose, and cellulose as well as lipids such as resins) [43]. At 600 °C this fraction was condensed by pyrosynthesis into larger aromatic structures increasing the BCHyPy [13,23,44]. The highly polycondensed aromatic moieties of BCHyPy cannot be cracked into volatile compounds analyzable by GC-MS.…”
Section: 2 Bchypy Fractionmentioning
confidence: 99%